Chronic Repetitive Mild Traumatic Brain Injury Results in Reduced Cerebral Blood Flow, Axonal Injury, Gliosis, and Increased T-Tau and Tau Oligomers. Issue 7 (July 2016) - Ojo, Joseph O.; Mouzon, Benoit; Algamal, Moustafa; Leary, Paige; Lynch, Cillian; Abdullah, Laila; Evans, James; Mullan, Michael; Bachmeier, Corbin; Stewart, William; Crawford, Fiona
Abstract : Exposure to repetitive mild traumatic brain injury (mTBI) is a risk factor for chronic traumatic encephalopathy, which is characterized by patchy deposition of hyperphosphorylated tau aggregates in neurons and astrocytes at the depths of cortical sulci. We developed an mTBI paradigm to explore effects of repetitive concussive-type injury over several months in mice with a human tau genetic background (hTau). Two injuries were induced in the hTau mice weekly over a period of 3 or 4 months and the effects were compared with those in noninjured sham animals. Behavioral and in vivo measures and detailed neuropathological assessments were conducted 6 months after the first injury. Our data confirm impairment in cerebral blood flow and white matter damage. This was accompanied by a 2-fold increase in total tau levels and mild increases in tau oligomers/conformers and pTau (Thr231) species in brain gray matter. There was no evidence of neurofibrillary/astroglial tangles, neuropil threads, or perivascular foci of tau immunoreactivity. There were neurobehavioral deficits (ie, disinhibition and impaired cognitive performance) in the mTBI animals. These data support the relevance of this new mTBI injury model for studying the consequences of chronic repetitive mTBI in humans, and the role of tau in TBI.